Analysis Of The Influence Of Digital Awareness, Security, And Ethical Responsibility In Student Interaction In Aviation Educational Institutions - Muhammad Caesar Akbar; Stifhany Margaretha (CERED Indonesia Institute, 2025)
This study aims to analyze communication dynamics within student WhatsApp groups and the influence of digital ethics on awareness, security, openness, orderliness, and responsibility. A qualitative approach was employed through in-depth interviews and participatory observation involving 20 students. The ethics findings indicate that appropriate implementation of digital enhances communication effectiveness, strengthens trust, and fosters a conducive learning environment. This aligns with Chen (2019), who emphasizes the importance of rules in managing online group dynamics and fostering accountability. Smith and Duggan (2016) also highlighted the role of messaging platforms like WhatsApp in improving peer collaboration.